Thermal-responsive activation of engineered bacteria to trigger antitumor immunity post microwave ablation therapy - Yumin Wu; Bo Liu; Yifan Yan; Chuntao Gong; Kaiwei Wang; Nanhui Liu; Yujie Zhu; Maoyi Li; Chunjie Wang; Yizhe Yang; Liangzhu Feng; Zhuang Liu (Nature Communications)
Abstract Incomplete tumor removal after microwave ablation (MWA), a widely used hyperthermia-based therapy, can result in tumor recurrence. Herein, attenuated Salmonella typhimurium VNP20009 is engineered to release interleukin-15&interleukin-15-receptor-alpha (IL-15&IL-15Rα) in response to mildly elevated temperature. Such 15&15R@VNP colonizes in tumors upon intravenous injection, and the expression of IL-15&IL-15Rα is triggered by MWA. Anti-tumor immune responses are elicited, efficiently suppressing tumor growth even after incomplete microwave ablation. We further design VNP20009 with thermal-responsive co-expression of both IL-15&IL-15Rα and soluble programmed cell death protein (sPD-1). Such sPD-1-15&15R@VNP can also reverse the functional suppression of immune cells driven by PD-1/PD-L1 axis, reinvigorating progenitor exhausted T cells, a critical subset of cytotoxic T lymphocytes responsive to immune checkpoint blockade. Such thermal-responsive engineered bacteria are thus a promising adjuvant therapy to potentiate tumor ablation therapies via effectively activating antitumor immunity.